Safety assessment of the process NGR LSP used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials (FCM); Claude Lambré; Riccardo Crebelli; Maria deSilva; Koni Grob; Maria Rosaria Milana; Marja Pronk; Gilles Rivière; Mario Ščetar; Georgios Theodoridis; Els Van Hoeck; Nadia Waegeneers; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Contact Materials (FCM) assessed the safety of the recycling process NGR LSP (EU register number RECYC328). The input is hot washed and dried poly(ethylene terephthalate) (PET) flakes mainly originating from collected post‐consumer PET containers, with no more than 5% PET from non‐food consumer applications. The flakes are dried (step 2), melted in an extruder (step 3) and decontaminated during a melt‐state polycondensation step under high temperature and vacuum (step 4). In step 5, the material is granulated. Having examined the challenge test provided, the Panel concluded that the melt‐state polycondensation (step 4) is critical in determining the decontamination efficiency of the process. The operating parameters to control the performance of step 4 are the pressure, the temperature, the residence time and the characteristics of the reactor. It was demonstrated that this recycling process ensures that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.0481 or 0.0962 μg/kg food, depending on the molar mass of a contaminant substance. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, including drinking water, for long‐term storage at room temperature or below, with or without hot‐fill. Articles made of this recycled PET are not intended to be used in microwave and conventional ovens and such uses are not covered by this evaluation.